Hydraulics and Pneumatics : a technician's and engineer's guide - Parr, E. A. (E. Andrew) (Butterworth-Heinemann, 2011)
Nearly all industrial processes require objects to be moved, manipulated or subjected to some sort of force. Such movements and manipulations are frequently accomplished by means of devices driven by liquids (hydraulics) or air (pneumatics), the subject of this book. Hydraulics and Pneumatics is written by a practicing process control engineer as a guide to the successful operation of hydraulic and pneumatic systems for all engineers and technicians working with them. Keeping mathematics and theory to a minimum, this practical guide is thorough but accessible to technicians without a.